Chalcogenide perovskites: enticing prospects across a wide range of compositions and optoelectronic properties for stable photodetector devices - Shilpa Mariam Samuel; Sadasivan Shaji; David Avellaneda Avellaneda; Bindu Krishnan (Nano Express)
Photodetectors are indispensable components of many modern light sensing and imaging devices, converting photon energy into processable electrical signal through absorption, carrier generation and extraction using semiconducting thin films with appropriate optoelectronic properties. Recently, metal halide perovskites have demonstrated groundbreaking photodetector performance due to their exceptional properties originating from their perovskite structure. However, toxicity and stability remain challenges for their large-scale applications. Inspired by the perovskite structure, intense investigation in search of highly stable, non-toxic and earth abundant materials with superior optoelectronic features has led to the discovery of chalcogenide perovskites (CPs). These are unconventional semiconductors with the formula ABX _3 , where A and B are cations and X is a chalcogen, which covers the compounds with the corner sharing perovskite structures of type II-IV- VI _3 compounds (II = Ba, Sr, Ca, Eu; IV = Zr, Hf; VI = S, Se) and III _1 -III _2 -VI _3 compounds (III _1 and III _2 = Lanthanides, Y, Sc; VI = S, Se). The increased coordination and ionicity in these compounds contribute to their excellent charge transport properties and exceptionally high optical absorption coefficient (> 10 ^5 cm ^−1 ). The present review encompasses theoretical analysis that provides electronic band structures and the orbital contributions that support the excellent optoelectronic properties. Furthermore, the challenging thin film deposition, characterizations, and their application in photodetection focusing on BaZrS _3 -which is the most studied one, are ascribed. Additionally, we suggest prospects that can bring out the true potential of these materials in photodetection and photovoltaics.